Aboriginal fathering discourses: what does the data tell us about educational involvement with their children? - Prehn, Jacob (My University, 2019)
Primary caregivers play an important role in the lives of Indigenous children. They help them to grow up strong and achieve educational success. The colonisation of Australia has resulted in a negative discourse portraying Aboriginal and/or Torres Strait Islander men as drunks, low-achievers and poor fathers. This paper aims to challenge this stereotype by using data from the Longitudinal Study of Indigenous Children. A univariate and bivariate analysis is undertaken to examine Indigenous and non-Indigenous fathers and involvement in the lives and education of their children. Results show no significant difference between Indigenous and non-Indigenous fathers and that Aboriginal and/or Torres Strait Islander fathers are positively engaged in their children’s education despite experiencing structural disadvantages. These findings challenge the discourse that Aboriginal and/or Torres Strait Islander men are poor fathers. To help Indigenous children grow up strong, Indigenous fathers need support to overcome the negative effects of colonisation.
Keywords: Disadvantage, adversity and resilience; Childhood and child development; Families and relationships